2023
DOI: 10.1136/bmjopen-2022-067384
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antimicrobial susceptibility pattern and multidrug resistance of methicillin-resistantStaphylococcus aureusisolated from clinical samples at a tertiary care teaching hospital: an observational, cross-sectional study from the Himalayan country, Nepal

Prashant Adhikari,
Deepak Basyal,
Junu Richhinbung Rai
et al.

Abstract: ObjectiveWe sought to determine the prevalence and antimicrobial susceptibility pattern of methicillin-resistantStaphylococcus aureus(MRSA) isolated from the clinical samples at a tertiary care hospital in Nepal.MethodsCross-sectional, observational study design.Study settingThe study was carried out at a tertiary care facility, the largest public hospital, Tribhuvan University Teaching Hospital (TUTH), Nepal.ParticipantsA total of 7433 clinical samples from hospital inpatients and outpatients available in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The highest prevalence of S. aureus was found in pus and blood, similar to other studies. [18][19][20] The highest isolation rate of S. aureus in pus and blood in this study could be partly due to S. aureus is a normal flora of skin that can enter the body through cracks, abrasion, cuts, surgical incisions, burn, and intravenous catheter and causes pyogenic infection. 21 The antimicrobial susceptibility testing in the present study demonstrated high resistance profiles of S. aureus isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest prevalence of S. aureus was found in pus and blood, similar to other studies. [18][19][20] The highest isolation rate of S. aureus in pus and blood in this study could be partly due to S. aureus is a normal flora of skin that can enter the body through cracks, abrasion, cuts, surgical incisions, burn, and intravenous catheter and causes pyogenic infection. 21 The antimicrobial susceptibility testing in the present study demonstrated high resistance profiles of S. aureus isolates.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in China, Zheng et al 5 noted that a majority of MRSA (71.1%) isolates were MDR. Additionally, the study of Adhikari et al 19 from clinical samples at a Tertiary Care Teaching Hospital in Nepal showed that 94.05% of the isolates were MDR in MRSA. In various contexts in Egypt, up to 79% of MDR-MRSA has been documented.…”
Section: Discussionmentioning
confidence: 99%